Facing a Health Threat in a Complex Information Environment: A National Representative Survey Examining American Adults' Behavioral Responses to the 2009/2010 A(H1N1) Pandemic. (February 2018) - Lin, Leesa; McCloud, Rachel F.; Jung, Minsoo; Viswanath, Kasisomayajula
Background . Recent A(H1N1) studies suggest that intrapersonal and interpersonal factors may exert influence on people's preventive behaviors for avoiding the flu during pandemics. Aims . Nonpharmaceutical interventions (NPIs) and vaccinations play key roles in containing disease transmission during a pandemic. We examined how intrapersonal and interpersonal factors influenced adoption of NPIs and vaccine uptake during the A(H1N1) pandemic of 2009. Method . The data come from a nationally representative sample survey of 1, 569 American adults. Hierarchical multivariable logistic regression was conducted to investigate the association between socioeconomic position, concern and knowledge about the threat, social networks for health advice or health care seeking, health consultations with doctors, and NPIs (including individual's social distancing behaviors and hygiene practices) and vaccine acceptance. Results . People with higher scores on health-related social networks, more knowledge or concern about A(H1N1), and those who have consulted their doctor were more likely than others to adopt NPIs. There was a significant association between being concerned about A(H1N1), having consulted a doctor, and seeking a vaccine. Conclusions . These findings suggest that interpersonal communication factors, such as health-related social networks and consultations with doctors, and intrapersonal factors, such as concern and knowledge, play a critical role in NPIs and vaccine uptake during pandemics and offer avenues for intervention.